Analysis of Students’ Ability in Writing Descriptive Text (A Case Study in SMA Negeri 5 Karawang) - Siti Munawaroh (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The aim of this study was to determine the students’ ability in writing descriptive text at class X7 SMA Negeri 5 Karawang; to answer the formulation of research questions; and the writer used qualitative approach by using case study method. This study was conducted at SMA Negeri 5 Karawang and took six students of class X7 as participants. The data were collected by observation and documentation. In the documentation stage, the writer collected descriptive texts written by students and then analyzed the texts by using systemic functional linguistic (SFL). The findings of this study indicated that the students of high achievement had been able to write descriptive text well, while the students of middle and low achievement have employed the schematic structure of descriptive text, but they still made many mistakes in applying linguistic features.